SECONDARY SCHOOL PRINCIPALS' LEVEL OF PREPAREDNESS AND ADOPTION OF NATIONAL EDUCATION MANAGEMENT INFORMATION SYSTEM IN KEIYO NORTH SUB-COUNTY, KENYA - Kasimiri, Samson; Sang, Professor; Shadrack , Saina; Beru, Moses (African Journal of Education and Practice, 2021)
Purpose: The study investigated the level of preparedness of secondary school Principals to adopt the National Education Management Information System (NEMIS) in Keiyo North Sub-County, Elgeiyo-Marakwet County in Kenya. Methodology: It was an explanatory research based on the Unified Theory of Acceptance and Use of Technology (UTAUT) and the public choice theory. A target population of 30 secondary schools Principals and 30 HODs in charge of ICT in Keiyo North Sub-County schools consisting of Boarding and Day secondary schools was used. This formed a population of 60. The schools were classified as National, Extra-County, County and Sub-County secondary schools. This ensured that all the sub-groups were proportionately represented. Quantitative data was collected using close-ended questionnaires and analyzed using descriptive and inferential statistics. A model was developed through regression analysis. Findings: Results indicate that the sub-variable of Principal's level of preparedness (acceptance, training and skills, and ICT infrastructure) had a statistically significant positive effect on adoption of NEMIS in secondary schools. The finding of this study is useful to the Ministry of Education (MOE) in planning purposes. The constructs of Principal's level of preparedness (acceptance, training and skills and ICT infrastructure) positively and significantly correlated with adoption of NEMIS and as these constructs are enhanced, adoption of NEMIS receives a positive boost. Unique Contribution to Theory Practice and Policy: The study points out that use of technology is a function of acceptance by the user and is in line with the postulates of UTAUT theory that drove this study. It is therefore recommended that managers in the education circles should pay greater attention to the postulates of UTAUT theory for effective implantation of ICT driven programs like NEMIS. The study further points out that for any government policy to succeed, those in authority should allocate resources for public interest to support such policy rather than follow their own self-interest as pointed out by the public choice theory.